USP10 suppresses tumor progression by inhibiting mTOR activation in hepatocellular carcinoma. (1st November 2018) - Lu, Chang; Ning, Zhen; Wang, Aman; Chen, Di; Liu, Xiaolong; Xia, Tian; Tekcham, Dinesh Singh; Wang, Wen; Li, Tongming; Liu, Xiumei; Liu, Jing; Qi, Huan; et al.
Abstract: Dysregulation of deubiquitination pathway is associated with poor prognosis in cancers such as hepatocellular carcinoma (HCC). The mammalian target of rapamycin, mTOR, has become an attractive cancer therapeutic target in HCC. However, whether and how aberrant expression of deubiquitination pathway regulates mTOR pathway has remained elusive. Here we report that ubiquitin-specific protease 10 (USP10) functions as a tumor suppressor which inhibits mTOR pathway by stabilizing PTEN and AMPKα in HCC cells. Mechanistically, USP10 interacts and stabilizes PTEN and AMPKα by inhibiting their polyubiquitylation. This stabilization in turn inhibits AKT phosphorylation and mTOR Complex1 (mTORC1) activation. In human liver cancer, USP10 expression is downregulated in HCC tumor tissues across three independent HCC cohorts, and lower-expression of USP10 will generate poor prognosis outcome. Collectively, our results uncover an undescribed mechanism where USP10, as a tumor suppressor, negatively regulates mTORC1 activation and AKT phosphorylation by stabilizing AMPKα and PTEN in HCC cells. This study sheds light on the theoretical basis of mTOR signaling pathway-oriented targeting treatment in clinic. Highlights: USP10 is significantly downregulated and associated with poor prognosis in HCC. USP10 stabilizes PTEN and AMPKα by inhibiting PTEN and AMPKα polyubiquitylation. USP10 inhibits hepatocellular carcinoma growth in vivo by inhibiting mTOR signaling pathway.